(3GdbUjOI GdOGeZI aj GdeaGNQI Hjf bHGFd bMWGf hYOfGfs - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s ((3Ydi Hf RjO Hf CMeO Hf jMji Hf CHj jMji s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdaQO GdUeO CdG jG OGQ dhdG JfWbjfG aEfG SGFdhf heNHQhfG s
(3BNQgG (B:s
(3hMSHc Cf OGA GdeQA jVMi Ydjg ddYOGI dg eYjfG hBNQ GdTQM (B: (3hEfi ef geOGf ai SQ SQgG Edi Bd YHO ef Jcjd hCOgeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3CLGH HgG GdeDda GdMSf Hf CMeO Hf jYbhH GdgeOGfi GdcejJ Hf RjO GdCSOi hbO aSQgG hTQMgG CMO JdGejP GdgeOGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs